The effect of personal and professional cultural values towards the marketing ethics of academicians - Chuah, Chin Wei; Adam, Mohamad Zainol Abidin; Hoe, Chee Hee (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
This study assesses the personal cultural values and professional values of academicians in regards to marketing ethics.This research uses Singhapakdi and Vitell’s (1993) marketing norms scale and professional value scale together with Yoo and Donthu’s (2002) three dimensional measures of culture operationalised at the individual level. The findings showed that Uncertainty Avoidance and Professional Values influenced academicians’ marketing ethics.It is therefore suggested that managers should look into methods and ways of cultivating professionalism among academicians in order for them to possess good marketing ethics.The findings also showed that demographic factors such as age, gender, years of working experience, academic qualification do not have any influence on academicians’ marketing ethics. Other implications of the study were also discussed.